Analysis Of Career Development And Performance Appreciation For BPJS Employment Employees At The Medan City Branch Office And The Medan North Branch Office - Rizal Ahmad (International Journal of Economics Accounting and Management, 2024)
The purpose of this study is to look into how employee performance at BPJS Employment's Medan City and Medan North branches is affected by career development and awards. All 68 employees of the BPJS Employment Medan Kota Branch Office and the Medan Utara Branch Office make up the study's population. A total of 66 respondents' samples were collected. Purposive sampling is the method of sampling that is employed. This study was carried out in 2023. A questionnaire was used to obtain the data. This study employs a quantitative and associative methodology. SPSS version 20.0 was used for data processing. Multiple linear regression was employed as the analysis method. The study's findings indicate that the F-value is 236.992 with a significance of 0.000, the t-value for career growth is 4.805 with a significance of 0.000, and the t-value for incentives is 4.946 with a significance of 0.000. The performance of employees at the BPJS Ketenagakerjaan Medan City Branch Office and the Medan North Branch Office is thus positively and significantly impacted by career development and awards, whether partially or concurrently.